Exchange Rate Variability Inside and Outside the EMU - Lennart Bergbom (Uppsala University, Department of Economics, 1998)
An often heard view is that exchange rate variability will decrease for a country that joins the EMU. This is not necessarily true. Both real and nominal exchange rate variability increase under certain circumstances when asymmetric demand shocks occur inside or outside the union. These results are obtained theoretically within a standard international macro-model but they also remain valid in a numerical simulation of this model.
urn:nbn:se:uu:diva-2435
Keywords: F31; F33; F36; F41; 330; Exchange rate variability; EMU; asymmetric shocks